Factors Related To Eye Fatigue In Computer Users In The Regional Office Of The Ministry Of Religious Affairs Riau Province: Faktor – Faktor Yang Berhubungan Dengan Kelelahan Mata Pada Pengguna Komputer Di Kantor Wilayah Kementerian Agama Provinsi Riau - Septiani Sustri; Firman Edigan; Raviola Raviola (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Eye fatigue is a strain in the eyes caused by a long-term disturbance of the sense of vision which is usually accompanied by an uncomfortable viewing condition. Based on interviews with 8 employees who work using computers daily, they generally work > 2 hours per day in front of the computer, experiencing headaches, pain in the eye muscles and blurry eyes. The purpose of this study was to determine the relationship between employee characteristics and work devices with eye fatigue in computer users. This study is a quantitative analytical study using a cross-sectional study design, with respondents of employees using computers at the Regional Office of the Ministry of Religious Affairs of Riau Province. The total sample in the study was 71 employees. The sampling technique is simple random sampling. The measuring instruments used are questionnaires, and measurements. The analysis used is univariate and bivariate with Chi-square statistical test. The results showed that there was a significant relationship between refractive abnormalities (Pvalue=0.011, OR value=7.636), computer use duration (Pvalue=0.041, OR value=8.769), eye visibility on the monitor screen (Pvalue=0.007, OR value=16.792) with eye fatigue. The results showed no significant relationship between length of service (Pvalue= 0.231, OR value=3.426) and eye fatigue. So there is a significant association between refractive abnormalities, the duration of computer use and the visibility of the eyes on the monitor screen against eye fatigue.